Chiral Aminated α‐Methylenebenzocycloalkenes from o‐Bromoaryl Aldehydes and Ketones. Issue 12 (7th March 2013) - Sirvent, Juan Alberto; Foubelo, Francisco; Yus, Miguel
Abstract: Chiral tert ‐butylsulfinyl imines3, which are easily prepared from the corresponding bromo carbonyl compounds1 and tert ‐butanesulfinamide (2 ), undergo a diastereoselective allylation by using indium metal and allyl bromide to give the corresponding homoallyl sulfinylamines4 . Treatment of compounds4 with a catalytic amount of palladium acetate and triphenylphosphane gives exo ‐methylene‐substitutedsulfinylamino)benzocycloalkenes5 (five‐ to seven‐membered rings) that are easily deprotected with hydrochloric acid to give chiral primary amines6 . Abstract : Enantioenriched nitrogen‐containing α‐methylenebenzocycloalkenes are prepared through a sequential diastereoselective indium‐promoted allylation of chiral N ‐ tert ‐butylsulfinyl imines and an intramolecular Heck reaction.